A Comparison of CNTFET and CMOS Technology through the Design of a SRAM Cell. (31st January 2019) - Marani, R.; Perri, A. G.
Abstract : In this paper we propose the design of a SRAM cell, based both on CNTFET and CMOS technology, in order to compare them. The first design is based on a CNTFET model, already proposed by us, while for the second one we use the BSIM4 model of the ADS library. In particular the MOSFET parameters, obtained using an evolution of previous Berkeley Predictive Technology Model (BPTM), are improved by us through parametric simulations to obtain performance of the MOSFET model comparable to the CNTFET one. At last we present the comparison between the two considered technologies, showing quantitatively the improvements obtained with CNTFET technology.